(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Evaluating time since death is an fundamental part of medico-legal investigations. Rigor Mortis is determined by routine convential method of corpus examination and detecting development of postmortem changes which are affected by many internal and external factors. The study was done on 100 medico-legal autopsies. Presence of Rigor Mortis in the cadavers was observed both in voluntary and involuntary muscles. Voluntary muscles were tested by gently moving the parts (eyelids, jaw) or by gently flexing the joints. Involuntary muscles like heart by slightly compressing it. Most of the cases belonged to 21-40 years of age group ( 45%) followed by 41-60 years (32%). 78% of the victims were males while only 22% were females .66% of the cases were reported to be the Road traffic accidents, 13% were poisoning cases, 7% natural death and 4% hanging. Majority of the cases seen were those of brought dead cases i.e; 57% and the hospital deaths recorded were 43%. 99% of victims were clothed. Mean maximum temperature was 33.86±6.6hrs and minimum temperature noted was 24.31±6.5hrs &percentage humidity recorded was 33.51±20.2 . In this study 95% Rigor Mortis was recorded in eyelids, 95% of Rigor Mortis was seen in jaw, 95% in the neck, 96% in the right upper limb, 94% in the left upper limb,80% cases in right lower limb and 80% in the left lower limb. Minimum Postmortem interval recorded was 4 hrs and maximum postmortem interval reported was 36 hrs. Mean PMI reported was 14.80±5.87 hrs. Majority of the cases were reported from two police stations Mullana, which were 46 in number and from Barara ,24 in number.